2003
DOI: 10.1002/adsc.200390057
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Conversions in Water. Part 22: Electronic Effects in the (Diimine)palladium(II)‐Catalysed Aerobic Oxidation of Alcohols

Abstract: The electronic effects in the (diimine)Pd-(II)-catalysed aerobic oxidation of alcohols were investigated from the viewpoint of both the catalyst and the alcohol. A −push±pull× mechanism is operative, where both electron-donating substituents on the benzyl alcohol (1 À 0.58) and electron-withdrawing groups on the 4,4'-disubstituted-2,2'-bipyridine ligand (1 0.18) increase the reaction rate. The results indicate partial reduction of the palladium centre in the transition state of the rate-limiting step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(58 citation statements)
references
References 53 publications
2
55
0
1
Order By: Relevance
“…Another specific point of the present Pd/SiO 2 -Al 2 O 3 catalyst is that all the substituted benzyl alcohols investigated here exhibit lower reactivities than benzyl alcohol. However, for many homogeneous Pd complex catalysts, [32,33] it has been reported that the reactivities of substituted benzyl alcohols with electron-donating substituents are higher than that of benzyl alcohol, while the presence of electron-withdrawing substituents decreases the reactivity. The same phenomenon has also been reported for some heterogeneous catalysts such as Ru(OH) x /Al 2 O 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another specific point of the present Pd/SiO 2 -Al 2 O 3 catalyst is that all the substituted benzyl alcohols investigated here exhibit lower reactivities than benzyl alcohol. However, for many homogeneous Pd complex catalysts, [32,33] it has been reported that the reactivities of substituted benzyl alcohols with electron-donating substituents are higher than that of benzyl alcohol, while the presence of electron-withdrawing substituents decreases the reactivity. The same phenomenon has also been reported for some heterogeneous catalysts such as Ru(OH) x /Al 2 O 3 .…”
Section: Resultsmentioning
confidence: 99%
“…This is also a quite unique observation because the benzyl alcohols with an electron-donating substituent, which can facilitate the b-hydride elimination, show higher reactivities in many homogeneous systems. [32,33] We speculate that the lower reactivity of the substrates with electron-donating substituents in our case may stem from the lower ability of chemisorption of these substrates on the Pd sites because of the steric hindrance. This further supports the speculation that both the coordinately unsaturated sites and the terrace sites are required for obtaining a high intrinsic TOF for benzyl alcohol conversion.…”
Section: Structure-sensitivity Of Pd Nanoparticles-catalyzed Oxidatiomentioning
confidence: 93%
“…[19] From 3a, several routes led to differently substituted 4,4'-biypridines (4a-6a) [19][20][21] (see Figure 2). Starting from commercially available mono-oxidised, mono-nitrated 10a, 11a was produced similarly to 5a.…”
Section: Mediator Preparationmentioning
confidence: 99%
“…Many highly efficient catalysts for the aerobic oxidation of alcohols have been developed recently using palladium [8][9][10][11], platinum [12], ruthenium [13] and rhodium complexes [14][15][16][17]. In the interest of sustainability, there has been significant development in the use of more abundant and cheaper transition metals such as iron [18][19] and copper as active catalysts.…”
Section: Introductionmentioning
confidence: 99%